While no one was watching - Conly, Jane Leslie (New York : HarperTrophy, 2000)
When two brothers steal a rabbit from a back yard in the rich part of town, the incident brings about their collision with other children from a background very different from their own.
5.9
5-8
5-8
Wilson's Children
Wilson's Junior High School
Elem. School Library Collection
Keywords: City and town life -- Fiction; Brothers -- Fiction; Rabbits -- Fiction; City and town life -- Fiction; Brothers -- Fiction; Rabbits -- Fiction